The Study of the Effect of Impeller Shape and Location on the Mixing Behaviour Using CFD Modeling - Mohd Hafizudin Bin Rozali, Mohd Hafizudin (Universiti Teknologi Petronas, 2010)
This project presents on predicting the flow and mixing behaviour inside the mixing tank and to investigate the effect of impeller design or shape and location on the mixing characteristic. Impeller location is defined as the distance between the base of the tank and the surface below the impeller’s blade. It is generally believed that mixing in stirred tank is dominated by the turbulent diffusion or dispersion compared to the convective mixing. Replace a new impeller inside the tank without properly tested, designed and modelling will cost much. If bad mixing occurs, it may lead to increase cost due to further modification and the production also will decrease. Prototype also incurred cost to build and operate it and require looking like the same as the real one. Therefore, in this project, FLUENT 12.0.6 will be used to simulate the flow inside the mixing tank. The impeller shape and location will be investigated to know how they will affect the flow and the mixing behaviour inside the mixing tank. The existing mesh created by GAMBIT® for the tutorial will be re-used and modified its impeller design and to simulate the flow by using FLUENT®. The objective of this project is to predict the result which design for the impeller is the best for better and efficient mixing in the tank. It is clearly shown that the lower impeller location inside the tank gives better mixing condition than others. The time to reach settling time for this impeller’s location also is optimum and acceptable. Recreate the impeller shape cause the weight of impeller to increase thus reducing the impeller’s rotational speed. This will lessen the efficiency of the mixing tank.